FOXO3-induced microRNA-128-3p promotes the progression of spinal cord injury in mice via regulating NLRP3 inflammasome-mediated pyroptosis - Yang, Shuo; Guan, Yunzhi; Zheng, Chaojun; Xia, Xinlei; Ma, Xiaosheng; Jiang, Jianyuan (Frontiers in Immunology, 2025)
BackgroundSpinal cord injury (SCI) remains a severe condition with an extremely high disability rate and complex pathophysiologic mechanisms. Pyroptosis, an inflammatory form of cell death triggered by certain inflammasomes, has a key role in a variety of inflammatory diseases, including SCI. However, it is unclear whether microRNAs (miRNAs), novel regulators in the SCI, are involved in SCI-induced pyroptosis.MethodsTwo GEO miRNA expression profiles (GSE158195 and GSE90452) were downloaded, and the differentially expressed miRNAs were analyzed by bioinformatics methods. An in vivo animal model and an in vitro cellular model of SCI were constructed in female C57BL/6 mice and BV-2 cells for studying the possible roles of FOXO3, miR-128-3p and NLRP3-mediated pyroptosis in SCI. Markers of ROS, cell pyroptosis and inflammation were measured by RT-qPCR, Western blotting, immunofluorescence, flow cytometry, and enzyme-linked immunosorbent assays. Histopathological changes in spinal cord tissue were detected using hematoxylin and eosin and immunohistochemical. The Basso–Beattie–Bresnahan (BBB) score was used to evaluate the motor function of mice in each group.ResultsBioinformatics analysis of GSE158195 and GSE90452 datasets revealed a significant downregulation of miR-128-3p, a phenomenon that was consistently observed in the SCI mice model. Functionally, miR-128-3p upregulation improved functional behavioral recovery, relieved pathological injury, repressed oxidative stress, and alleviated pyroptosis and inflammation in the mouse SCI models. We also confirmed that Thioredoxin-interacting protein (TXNIP) was the target gene of miR-128-3p, and overexpression of TXNIP can effectively reverse the improvement of miR-128-3p in SCI cell model. Moreover, we found that transcription factor FOXO3 facilitated miR-128-3p expression, and its overexpression resulted in similar effects of miR-128-3p in the SCI cell model.ConclusionTo the best of our knowledge, this is the first report demonstrating miR-128-3p improved secondary injury in SCI through the modulation of cell pyroptosis pathway. Our results suggest that FOXO3/miR-128-3p/TXNIP/NLRP3-mediated pyroptosis axis may be a potential therapeutic target for SCI.